Mycorrhizae Alter Toxin Sequestration and Performance of Two Specialist Herbivores - Meier, Amanda R.; Hunter, Mark D. (Frontiers in Ecology and Evolution, 2018)
Multitrophic species interactions are shaped by both top-down and bottom-up factors. Belowground symbionts of plants, such as arbuscular mycorrhizal fungi (AMF), can alter the strength of these forces by altering plant phenotype. For example, AMF-mediated changes in foliar toxin and nutrient concentrations may influence herbivore growth and fecundity. In addition, many specialist herbivores sequester toxins from their host plants to resist natural enemies, and the extent of sequestration varies with host plant secondary chemistry. Therefore, by altering plant phenotype, AMF may affect both herbivore performance and their resistance to natural enemies. We examined how inoculation of plants with AMF influences toxin sequestration and performance of two specialist herbivores feeding upon four milkweed species (Asclepias incarnata, A. curassavica, A. latifolia, A. syriaca). We raised aphids (Aphis nerii) and caterpillars (Danaus plexippus) on plants for six days in a fully factorial manipulation of milkweed species and level of AMF inoculation (zero, medium, and high). We then assessed aphid and caterpillar sequestration of toxins (cardenolides) and performance, and measured defensive and nutritive traits of control plants. Aphids and caterpillars sequestered higher concentrations of cardenolides from plants inoculated with AMF across all milkweed species. Aphid per capita growth rates and aphid body mass varied nonlinearly with increasing AMF inoculum availability; across all milkweed species, aphids had the lowest performance under medium levels of AMF availability and highest performance under high AMF availability. In contrast, caterpillar survival varied strongly with AMF availability in a plant species-specific manner, and caterpillar growth was unaffected by AMF. Inoculation with AMF increased foliar cardenolide concentrations consistently among milkweed species, but altered aboveground biomasses and foliar phosphorous concentrations in a plant species-specific fashion. Increased herbivore sequestration of cardenolides followed AMF-mediated increases in foliar cardenolide concentrations. Aphid performance declined with increasing foliar cardenolide concentrations, while caterpillar survival increased with aboveground biomass. Our findings suggest that by altering plant phenotype, the availability of AMF in soil has the potential to influence both top-down (via sequestration) and bottom up (via plant defense and nutrition) forces that operate on herbivores.